Seed Germination and Grain Quality of Rice as Affected by False Smut Disease (Bangladesh Rice Journal, 2019)
Rice false smut (RFSm) is a disease of interest globally and in Bangladesh. Its occurrence and spread have drawn attention since 2010 in the country. While many reports are available on the yield loss from the disease, little is known of its effect on grain quality. Besides, there has been no information on how RFSm affects the seed quality with respect to germination. This study attempted evaluation of seed germination and grain quality of rice as affected by false smut disease. Three years’ study provided strong indication of inferior milling outturn and head rice yield in RFSm contaminated seeds. Results further revealed reduced amylose content and increased protein content in the contaminated seeds. Tendency in reduced seed germination, and less cooking time was observed in RFSm contaminated seeds. Future research is suggested to fully understand those causations.Bangladesh Rice j. 2018, 22(1): 1-7